EFEK BIAYA LINGKUNGAN TERHADAP PENGUNGKAPAN EMISI KARBON PADA PERUSAHAAN ENERGI DI INDONESIA - Sutomo, Ibnu; Ridhawati, Rakhmi (Universitas Lambung Mangkurat, 2023)
The world currently faces issues related to climate change. Climate change poses a threat to the lives of all living beings in the form of extreme temperature increases, an increased potential for natural disasters, food crises, rising sea levels, the endangerment of flora and fauna, and heightened health risks. The proliferation of global warming issues has made stakeholders more environmentally conscious, even more aware of a company's environmental impact. The aim of this research is to understand the model of detecting Carbon Emissions Disclosure with determinants based on the Triple Bottom Line, one of which is Environmental costs. The research method involved a population of energy sector companies listed on the Indonesian Stock Exchange (BEI) for the period 2016-2020, as the energy sector has the largest environmental impact. The variable used in this research represents the triple bottom line, which is environmental costs. The analysis technique used was Eviews due to the panel data used. The research results indicate that environmental costs do not have a significant impact on carbon emissions disclosure.